1996
DOI: 10.1074/jbc.271.11.5988
|View full text |Cite
|
Sign up to set email alerts
|

Positive Regulation of cdc2 Gene Activity by Protein Phosphatase Type 2A

Abstract: Several lines of evidence indicate that serine/threonine protein phosphatases may act as negative regulators of cellular growth. For example, treatment of cells with the tumor-promoter okadaic acid, an inhibitor of certain types of these phosphatases, resulted in the increased expression of several proto-oncogenes, indicating a negative role of the respective phosphatases in gene regulation. However, it was puzzling to find that okadaic acid-treated cells, even in the presence of highly expressed proto-oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
(32 reference statements)
0
22
0
Order By: Relevance
“…Our results are consistent with previous studies in NIH 3T3 cells showing that okadaic acid causes a G 1 arrest that correlates with decreased pRB phosphorylation, decreased CDK activity, and a block in cyclin A, CDC2, and CDK2 expression (31). Consistent with a role in transcriptional regulation of CDC2, transient expression of the PP2A catalytic subunit can positively regulate CDC2 gene expression (54). However, the effects of OA may depend on the cell type as OA caused induction rather than repression of cyclin A, cyclin B, and CDC2 in transformed cells (55).…”
Section: Discussionmentioning
confidence: 81%
“…Our results are consistent with previous studies in NIH 3T3 cells showing that okadaic acid causes a G 1 arrest that correlates with decreased pRB phosphorylation, decreased CDK activity, and a block in cyclin A, CDC2, and CDK2 expression (31). Consistent with a role in transcriptional regulation of CDC2, transient expression of the PP2A catalytic subunit can positively regulate CDC2 gene expression (54). However, the effects of OA may depend on the cell type as OA caused induction rather than repression of cyclin A, cyclin B, and CDC2 in transformed cells (55).…”
Section: Discussionmentioning
confidence: 81%
“…5B). In order to specifically examine the role of PP2A, we used okadaic acid (OA) and endothall, which are preferential inhibitors of this enzyme (10,22,26). We found that treatment of CH12 B cells with 300 nM okadaic acid or 50 M endothall led to phosphatase inhibition as measured by Western blotting with antiphosphoserine antibodies, as well as increased AID-S3 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, PP2A appears to be a key regulator of the level of AID phosphorylation at S3, since defined pharmacological PP2A inhibitors augment AID-S3 phosphorylation in vivo. Calyculin inhibits both PP2A and PP1 equally (50% inhibitory concentration [IC 50 ], 1 nM), okadaic acid has a Ͼ100-fold-higher affinity for PP2A (IC 50 , 1 nM) (10,22), and endothall is a PP2A-specific inhibitor (26). Each of these inhibitors augments AID-S3 phosphorylation in stimulated B cells and also inhibits CSR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture and Transfection-Mouse NIH3T3 and human HeLa cells were grown in 10% calf serum/Dulbecco's modified Eagle's medium as described (25). Transfections were performed in 6-cm tissue culture dishes using the calcium-phosphate-DNA precipitation technique.…”
Section: Methodsmentioning
confidence: 99%